Maturation of the catalytic alpha-subunit of Na,K-ATPase during intracellular transport (The Rockefeller University Press, 1987)
The protease sensitivity of the catalytic alpha-subunit of Na,K-ATPase during intracellular transport along the exocytic pathway has been investigated in two amphibian epithelial cell lines. Controlled trypsinolysis followed by immunoprecipitation of cell homogenates or microsomal fractions from [35S]methionine pulse-chased A6 kidney cells revealed distinct cleavage patterns by SDS-PAGE. Shortly after synthesis (7-min pulse), the 98-kD alpha-subunit is fully sensitive to trypsin digestion and is cleaved into a 35-kD membrane-bound and a 27.5- kD soluble peptide. With a 15-min pulse, 10% of the newly synthesized polypeptide becomes resistant to trypsin digestion. With longer chase time, the proportion of protease-resistant alpha-subunit further increases. Concomitantly, the alpha-subunit acquires the ability to undergo cation-dependent conformational transitions, as reflected by distinct tryptic digest patterns in the presence of Na+ or K+. Similar results were obtained in TBM cells, a toad bladder cell line. Our data indicate that the catalytic subunit of Na,K-ATPase is structurally rearranged during intracellular transport from its site of synthesis to its site of action at the cell surface, a modification which might mark the functional maturation of the enzyme.